Expression of Shelterin Component POT1 Is Associated with Decreased Telomere Length and Immunity Condition in Humans with Severe Aplastic Anemia - Ting Wang; Shu-chong Mei; Rong Fu; Hua-quan Wang; Zong-hong Shao (Journal of Immunology Research)
Abnormal telomere attrition has been found to be closely related to patients with SAA in recent years. To identify the incidence of telomere attrition in SAA patients and investigate the relationship of telomere length with clinical parameters, SAA patients (n=27) and healthy controls (n=15) were enrolled in this study. Telomere length of PWBCs was significantly shorter in SAA patients than in controls. Analysis of gene expression of Shelterin complex revealed markedly low levels of POT1 expression in SAA groups relative to controls. No differences in the gene expression of the other Shelterin components—TRF1, TRF2, TIN2, TPP1, and RAP1—were identified. Addition of IFN-γ to culture media induced a similar fall in POT1 expression in bone marrow cells to that observed in cells cultured in the presence of SAA serum, suggesting IFN-γ is the agent responsible for this effect of SAA serum. Furthermore, ATR, phosphorylated ATR, and phosphorylated ATM/ATR substrate were all found similarly increased in bone marrow cells exposed to SAA serum, TNF-α, or IFN-γ. In summary, SAA patients have short telomeres and decreased POT1 expression. TNF-α and IFN-γ are found at high concentrations in SAA patients and may be the effectors that trigger apoptosis through POT1 and ATR.